Reactive Arthritis due to Shigella Infection after a Visit to Egypt: A Late Complication of an Intestinal Infection - Alwin Tilanus; Rembert Mertens; Lucie Seyler; Patrick Lacor; Brigitte Velkeniers (Case Reports in Gastrointestinal Medicine)
We describe a case of reactive arthritis following Shigella infection after a trip to Egypt. The diagnostic challenge and treatment of this acute medical condition are discussed.